LEARNING CREED MORALS WITH DEEP LEARNING APPROACH IN CLASS XII AT MADRASAH ALIYAH MUHAMMADIYAH 01 TEGALOMBO - Ismail; Tobroni; Faridi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
Creed Akhlak (Islamic Aqidah ) learning plays a strategic role in shaping students' character and personality in accordance with Islamic values. However, in practice, this learning often focuses on cognitive aspects and memorization, thus under-emphasizing the affective and psychomotor dimensions that are essential in values ​​education. Therefore, a deep learning approach is needed that emphasizes not only understanding the material but also the appreciation, reflection, and application of values ​​in real life. This study aims to examine the application of the deep learning approach in Aqidah Akhlak learning and its impact on the internalization of Islamic values ​​in grade XII students of MA Muhammadiyah 01 Tegalombo . This study used a qualitative method with a case study design. Data collection techniques were carried out through observation, in-depth interviews with teachers, the principal, and the deputy head of curriculum, documentation, and open-ended questionnaires to students. Data analysis was carried out using the interactive approach of the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research results show that the deep learning approach can increase students' active engagement in the learning process, deepening their understanding of the Aqidah Material morals, and encourage the internalization of values ​​such as honesty, responsibility, and tolerance in everyday life. Teachers implemented various strategies such as contextual case studies, reflective discussions, journal assignments, and grade presentations. Madrasah support contributed to the success of this approach. Despite challenges in terms of student readiness and time constraints, this approach was deemed effective in realizing Aqidah Learning morals that were more meaningful, transformative, and aligned with the goals of Islamic education.